Self-Management of Housing and Urban Commons: New Belgrade and Reflections on Commons Today - Dragutinovic, Anica (2022)
The concepts of collective management of housing and urban spaces are being revisited within the contemporary discussions about community-driven approaches and practices and, in particular, related to the revitalization of residential neighbourhoods. This research identifies the concepts of self-management and social ownership of housing in the post-World War II period in Yugoslavia as an important legacy of Yugoslav urban planning and housing policies. Although they were subsequently neglected, these concepts can contribute to contemporary global discussions about housing affordability and the role of community in ensuring spatial and social equality. New Belgrade mass housing blocks—the main site for testing the new dwelling concepts, in terms of both policies and modernist design—are the object of this research. The article is mainly a theoretical analysis of the issues of common interest and engagement, common good, and common spaces which played a decisive role in its design. The study applies interpretative and correlational research methods in re-theorizing these concepts and their underlying narratives. It traces how the perspectives on the collective practices and spaces evolved over time, revealing a correlation between changed social practices and the spatial deterioration of the New Belgrade mass housing blocks. The study highlights the importance of both collective practices and common spaces for addressing housing issues, emphasizing their instrumentality, and potentiality for rearticulating the dialogue between public and private, engaging citizens in interactive and inclusive decision-making and co-creation of the urban reality.